The systemic multivalue of municipal waste – entities and methods of creation, multidimensional character of effects - Sztangret, Izabela (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The municipal waste value creation sector is multi-faced and includes primary and secondary market players, commercial and non-profit enterprises, prosumers of various price segments and more. The multi-value of waste, which is the result of multi-entity relations, has a strategic nature, due to the achieved social good, in the long term, due to the concept of the circular economy, by taking into consideration the principles of the concept of integral marketing, at the interface of the waste stream component supplier and its recipient, on the secondary market or in a re-cycle to achieve a long-term strategic effect. Each of the three identified and described sub-areas of the system creation of multi-value municipal waste, through reduction, recycling, reuse and repurpose, suggests an orientation corresponding to the concept of 5R of the studied entities, which has already been described in the author’s publications and may constitute an area of in-depth research in the future.